Enhancement of dielectric properties of lead-free BCZT ferroelectric ceramics by grain size engineering. (March 2019) - Hanani, Z.; Mezzane, D.; Amjoud, M.; Fourcade, S.; Razumnaya, A.G.; Luk'yanchuk, I.A.; Gouné, M.
Abstract: Lead-free Ba0.85 Ca0.15 Ti0.9 Zr0.1 O3 (BCZT) ceramics had attracted much attention for the fabrication of microelectronic devices by virtue of their excellent dielectric, ferroelectric and piezoelectric properties. To understand the effects of both mean grain size and grain size distribution on the dielectric properties of lead-free Ba0.85 Ca0.15 Ti0.9 Zr0.1 O3 (BCZT) ferroelectric relaxors, an original method was proposed. It is based on the surfactant-assisted solvothermal processing coupled with low-temperature conventional sintering at 1250 °C. In this way, three highly dense BCZT with different mean grain size and dissimilar grain size distribution were designed. A significant increase of dielectric properties was obtained by a control of grain size and densification process. The dielectric constants measured were ranged from 5370 to 9646 and the dielectric loss was enhanced by 70%. Surprisingly, it was evidenced that there is unequivocal link between mean grain size with dielectric properties. Indeed, it was found that the presence of high density of refined grains leads to an improvement of dielectric properties due to an enhancement of densification. This work may provide a new strategy to design ferroelectric materials with enhanced properties. Graphical abstract: Image Highlights: Novel way for the synthesis of lead-free BCZT ferroelectric relaxors with different grain size and grain size distribution. Unfolding the effects of grain size and grain size distribution on the dielectric properties of lead-free BCZT ferroelectric ceramics. Design of highly dense BCZT with improved dielectric properties.